2008
DOI: 10.1029/2007jd008814
|View full text |Cite
|
Sign up to set email alerts
|

Global observations of HNO3 from the High Resolution Dynamics Limb Sounder (HIRDLS): First results

Abstract: [1] We present the first evaluation of the HNO 3 data product (version 2.04.09) from the High Resolution Dynamics Limb Sounder (HIRDLS) on the Earth Observing System (EOS) Aura satellite. The HIRDLS instrument obtains between 5000 and 7000 HNO 3 profiles per day. HIRDLS HNO 3 data are generally good over the latitude range of 64°S to 80°N and pressure range 100 to 10 hPa, with some profiles, depending on latitude, having useful information between 100 to 161 hPa. The individual profile ''measured'' precision i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 72 publications
2
14
0
Order By: Relevance
“…The MIPAS/MLS deviations reported here are in agreement with other comparisons reported by San- tee et al (2007) with the exception of the tropics around 31.6 hPa. Also Kinnison et al (2008) have observed similar high relative differences in a comparison study between MLS and HIRDLS over the tropics. Since the structure appears like a second minimum over the tropics only in MLS and not in MIPAS distributions, it is attributed to an unexplained problem with MLS HNO 3 dataset.…”
Section: Hnosupporting
confidence: 60%
“…The MIPAS/MLS deviations reported here are in agreement with other comparisons reported by San- tee et al (2007) with the exception of the tropics around 31.6 hPa. Also Kinnison et al (2008) have observed similar high relative differences in a comparison study between MLS and HIRDLS over the tropics. Since the structure appears like a second minimum over the tropics only in MLS and not in MIPAS distributions, it is attributed to an unexplained problem with MLS HNO 3 dataset.…”
Section: Hnosupporting
confidence: 60%
“…Accuracies of the retrieved data are described in detail in the validation papers [ Gille et al , 2008; Massie et al , 2007; Nardi et al , 2008; Coffey et al , 2008; Kinnison et al , 2008]. As a quick reference, temperature accuracy is ±0.5 K from 400 to 10 hPa (compare sondes), and ±1 K from 10 to 1 hPa (compare ECMWF).…”
Section: Summary and Data Statusmentioning
confidence: 99%
“…However, on the basis of characterizing the emission from the blockage, algorithms have been designed and implemented in the HIRDLS Level‐1 software to correct the measured radiances for the interfering signal. Through these correction algorithms, the retrievals of T, O 3 , HNO 3 , CFC‐11, CFC‐12, cloud top pressures, and aerosol extinction at 12.1 μ m have improved to the extent that these products have been validated, released, and used in scientific studies [ Gille et al , 2008; Massie et al , 2007; Nardi et al , 2008; Coffey et al , 2008; Kinnison et al , 2008; Alexander et al , 2008; Olsen et al , 2008]. As of this writing (June 2009), the latest version of these data is V004 (internally v2.04.19), which is the basis of the results and illustrations in this paper and is available from the Goddard Earth Sciences Data and Information Services Center (GES DISC) (http://daac.gsfc.nasa.gov).…”
Section: Introductionmentioning
confidence: 99%
“…The Sub-Millimetre Radiometer (SMR) on Odin has been in orbit since 2001 (Murtagh et al, 2002;Urban et al, 2005), and the Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) on Envisat, since 2002(Mengistu Tsidu et al, 2005Wang et al, 2007a,b;Fischer et al, 2008). The Aura satellite, launched in 2004, carries another MLS Santee et al, 2007) and the HIgh Resolution Dynamics Limb Sounder (HIRDLS) Kinnison et al, 2008). These instruments are described in more detail below, in the context of comparisons with ACE-FTS.…”
Section: Introductionmentioning
confidence: 99%